Improvement of Family Care Ability for Elderly with Depression through Psychoeducation Intervention Program - Ni Made Riasmini (Jurnal Ilmu dan Teknologi Kesehatan, 2020)
The increase in the incidence of depression in the elderly can affect the elderly and their families' quality of life. Depression in the elderly is mostly caused by a lack of knowledge, attitudes, and family behavior caring for the elderly. It has an impact on the increasing cases of older people with depression in the community. To prevent increasing depression cases, it is necessary to empower family potential and social support. This study aims to obtain a description of the Psychoeducation Intervention Program (PIP) on families' ability to care for older people with depression in the community. The research method used is a Quasi-experiment with control group design. The sample is families who have elderly with depression by screening using the Geriatric Depression Scale Short Form (GDS-SF). The number of samples was 68 for the intervention group and 68 for the control group—statistical test using dependent t-test, independent t-test, and Mancova test. The results showed an increase in knowledge, attitudes, and family behavior in caring for the elderly before and after PIP. There were differences in the family's ability to care for the depressed elderly between the intervention and control groups. The resulting psycho-educational intervention program can serve as a basis for policymakers and health service managers to carry out various interventions related to family empowerment.